Implementasi Akad Ijarah dalam Pemanfaatan Aplikasi Digital untuk Transparansi Pencatatan Keuangan UMKM - Sa’diyah, Halimatus; Nugroho, Didik Kusno Aji; Setiawan, Agus; Ligery, Finny; Mushodiq, Agus (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
In the digital era, technology-based financial recording applications have emerged as potential solutions; however, their use requires careful examination from an Islamic economic perspective to ensure compliance with Sharia principles. This study aims to analyze the implementation of the ijarah contract in the use of digital financial recording applications by MSMEs in Way Kanan Regency and to assess its role in enhancing financial transparency. The research employed a qualitative descriptive method, with data obtained through in-depth interviews with MSME owners and application providers, direct observation of application usage, and documentation of financial practices. The analysis combined the theoretical framework of the ijarah contract in Islamic jurisprudence with the concept of transparency in financial management. The findings indicate that digital applications are commonly used through subscription or service rental schemes, which reflect the nature of the ijarah contract, as the agreements are based on clear benefits without involving gharar or riba. Moreover, the applications improve the consistency of financial recording, simplify reporting, and reinforce transparency both internally and externally. These results suggest that ijarah-based digital applications can serve as strategic instruments in strengthening Sharia-compliant financial governance for MSMEs.